An enzyme that removes clathrin coats: purification of an uncoating ATPase (The Rockefeller University Press, 1984)
Uncoating ATPase, an abundant 70,000-mol-wt polypeptide mediating the ATP-dependent dissociation of clathrin from coated vesicles and empty clathrin cages, has been purified to virtual homogeneity from calf brain cytosol. Uncoating protein is present in cells in amounts roughly stoichiometric with clathrin. This enzyme is isolated as a mixture of monomers and dimers, both forms being active. ATP can support protein- facilitated dissociation of clathrin at micromolar levels; all other ribotriphosphates as well as deoxy-ATP are inactive. The clathrin that is released from cages consists of trimers (triskelions) in a stoichiometric complex with uncoating ATPase. These complexes with clathrin have little tendency to self-associate at neutral pH, and at acidic pH they interfere with the assembly of free clathrin. The possible existence and function of these complexes as clathrin carriers in cells would explain why uncoating protein is made in quantities equivalent to clathrin.